1986
DOI: 10.1002/j.1460-2075.1986.tb04503.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the transcriptional control regions of the copia transposable element

Abstract: The introduction of copia‐based vectors in Drosophila hydei cells results in their high‐level transient expression and the subsequent establishment of stably transformed cell lines containing multiple copies of vector integrated into host genomic DNA. Using transformation frequency and transient expression analysis as assays of promoter strength, we have defined the regions of copia essential for expression. We find that the essential sequences reside within the long terminal repeat, but 3′ to the site of init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1987
1987
1996
1996

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…Other genes that require downstream sequences for their expression include the adenovirus 2 major late transcription unit (41), the herpes simplex virus tk gene (13), the a-and ,B-globin genes when expressed in murine erythroleukemia cells (10,73), and the Drosophila transposible element copia (62). Like the downstream element of the SV40 late promoter, these elements may affect transcription, but it is also possible that they affect a posttranscriptional process.…”
Section: Discussionmentioning
confidence: 99%
“…Other genes that require downstream sequences for their expression include the adenovirus 2 major late transcription unit (41), the herpes simplex virus tk gene (13), the a-and ,B-globin genes when expressed in murine erythroleukemia cells (10,73), and the Drosophila transposible element copia (62). Like the downstream element of the SV40 late promoter, these elements may affect transcription, but it is also possible that they affect a posttranscriptional process.…”
Section: Discussionmentioning
confidence: 99%
“…This list of promoters is not meant to be comprehensive. Promoters from retrotransposons and LINE-like elements include 297 (Inouye et al 1986), copia (Sinclair et al 1986), Doc (Schneuwly et al 1987), F (Di Nocera et al 1983, G (Di Nocera 1988), I (Fawcett et al 1986), and joc (Mizrokhi et al 1988). Promoters from cellular genes include AbdominaI-B (DeLorenzi et al 1988), AntpP2 (Perkins et al 1988), bride of sevenless (Hart et al 1993), brown (Dreesen et al 1988), caudal (Mlodzik and Gehring 1987), E74 (Thummel et al 1989;Burtis et al 1990), E75 (Segraves and Hogness 1990), engrailed (Soeller et al 1988), glass (Moses et al 1989), Gs~ (guanine nucleotide-binding protein; Quan and Forte 1990), labial (Mlodzik et al 1988), nonmuscle myosin heavy chain (Ketchum et al, 1990), ras2 (Bishop et al 1988), singed (Paterson and O'Hare 1991), Stellate (Livak 1990), and white (O'Hare et al 1984).…”
Section: Etfiid Can Function In Both Basal and Activated Transcriptionmentioning
confidence: 99%
“…TAS1 may therefore play a role in Ty transcription in addition to mediating cellular gene activation. Interestingly, transcription of the closely related copia element of Drosophila appears to be controlled by sequences downstream from the RNA start site (42). It has, however, recently been suggested that the signals controlling Ty transcription and gene activation are distinct (43).…”
Section: -Aammilmentioning
confidence: 99%